Intra-Arterial Bone Marrow Mononuclear Cell Transplantation Correlates with GM-CSF, PDGF-BB, and MMP-2 Serum Levels in Stroke Patients: Results from a Clinical Trial. Issue 1 (January 2014) - Moniche, Francisco; Montaner, Joan; Gonzalez-Marcos, Jose-Ramon; Carmona, Magdalena; Piñero, Pilar; Espigado, Ildefonso; Cayuela, Aurelio; Escudero, Irene; De La Torre-Laviana, Francisco-Javier; Boada, Cristina; Rosell, Anna; Mayol, Antonio; et al.
Bone marrow mononuclear cell (BM-MNC) intra-arterial transplantation improves recovery in experimental models of ischemic stroke through secretion of cytokines and growth factors (GFs), enhancing neoangiogenesis, and enhancing neuroplasticity. In this study, we tested whether BM-MNC transplantation in stroke patients induces changes in serum levels of cytokines and GFs. A phase I/II trial was conducted in middle cerebral artery (MCA) stroke patients with autologous intra-arterial BM-MNC transplantation between 5 and 9 days after stroke. Follow-up was done for up to 6 months. Eight cases and nine controls were included, and the serum levels of granulocyte-macrophage colony-stimulating factor (GM-CSF), platelet-derived growth factor-BB (PDGF-BB), β nerve growth factor (β-NGF), and matrix metalloproteinases 2 (MMP-2) and 9 (MMP-9) were measured before and 4, 8, and 90 days after transplantation. The correlation of these serum levels with dose of cells and clinical outcomes was studied. A total of 1.59 × 10 8 (±1.21 × 10 8 ) BM-MNCs were injected in cases; of them 3.38 × 10 6 (±2.33 × 10 6 ) were CD34 + cells. There was a positive correlation between total BM-MNCs injected and levels of GM-CSF and PDGF-BB at 90 days after transplantation ( r = 0.929, p = 0.001 and r = 0.714, p = 0.047, respectively), and a negative correlation between total CD34 + cells injected and MMP-2 levels at 4 days after transplantation ( r = −0.786, p = 0.036). Lower plasma levels of MMP-2 at 4 days and higher levels of PDGF-BB at 90 days were associated with better functional outcomes during follow-up ( p = 0.019 and p = 0.037, respectively). When administered intra-arterially in subacute MCA stroke patients, BM-MNCs seem to induce changes in serum levels of GM-CSF, PDGF-BB, and MMP-2, even 3 months after transplantation, which could be associated with better functional outcomes. This manuscript is published as part of the International Association of Neurorestoratology (IANR) special issue of Cell Transplantation .